Quality of Eucheuma cottonii seaweed cultivated in Lampung waters. (January 2020) - Subaryono; Kusumawati, R
Abstract: This study was aimed to observe the quality of Eucheuma cottonii dried seaweed produced from seaweed farmers in Lampung, especially in its main production centers namely sub-district Ketapang, south Lampung. Seaweed was taken from three locations namely Ruguk, Legundi and Tri Dharma Yoga Village. The parameters observed were included seaweed moisture content, clean anhydrous weed (CAW), ash content, yield, and the quality of carrageenan produced. The results showed that seaweed moisture content ranged from 21.71 to 33.48%, CAW 37.53-40.72%, ash content 33.68-43.08%, and carrageenan yield 11.35-13.57%. From the results of the observation it was concluded that the quality of seaweed from Legundi Village was the best compared to other villages.